Hegemonic ideas in the history of autism: Hegemonic ideas in the history of autism (Revista de História da UEG (REVHIST), 2025)
This paper analyzes the history of autism spectrum disorder, exploring how influences from different periods and contexts have impacted the lives of autistic people and their families. During the Second World War, 1943, the first diagnosis of autism was made, which came to be regarded as a new condition; then, based on discourses from several media, the ideas of what autism and the autistic person are like began to be constructed through discourses from various media. These discourses, on the other hand, were supported by the scientific knowledge available, which received visibility at the time, impacting on the existence conditions of this group. However, it is important to emphasize that history is a narrative affected by gender relations and, in some historical periods, by the influence of hegemonic ideas. The paper contributes to understanding how stigmatized ideas about autism were created.Keywords: Autism. History of autism. Stigma.
Keywords: Autism. History of autism. Stigma.